Empathy and communication skills in health professionals who work with pediatric chronic diseases - Raba, Ivana (2021)
Pediatric chronic diseases have a high prevalence rate at the national level, however, little has been studied about the professional competencies necessary for intervention in these cases, which turn out to be important to achieve therapeutic goals. The objective of this study was to investigate the relationship between empathy and communication skills in health professionals who work with pediatric patients with chronic diseases. The sample is for convenience made up of 146 female health professionals (M = 37.22; SD = 9.83). The variables are evaluated online through the Personal Reactivity Index, the Scale of Communication Skills in Health Professionals and an ad-hoc Sociodemographic Questionnaire. The results achieved indicate a partial correlation between the study variables since, although the total constructs of empathy and communication skills have not correlated significantly, it is possible to observe a significant association between the following subdimensions: on the one hand, perspective taking (empathy) and respect (communication skills) (r= .193) and, on the other hand, personal discomfort and social skills (r= .274), components of empathy and communication skills respectively. In conclusion, the value of the links built with pediatric patients is highlighted, which, sustained on the basis of an assertive, empathic and communicative professional performance, could become a potential therapeutic resource.